Hidden information in paintings that manifests itself in the near infrared spectrum Skrivena informacija u slikarstvu koja se manifestira u bliskom infracrvenom spektru - Žiljak Vujić, Jana; Tepeš Golubić, Lidija; Jurečić, Denis; Matas, Maja (2019)
For each pigment and dye, we associate information about their absorption of light in the near infrared spectrum (NIR) at 1000 nm. Generally, pigments red, yellow, cyan blue, orange, white and “drap” (sandy brown) do not absorb NIR light. The NIR camera does not distinguish, recognize or “see” them, so the NIR photo is white. Such colors are marked with the letter "V" (visual, VIS). The area of green pigments (in our language, “zeleno” = green) is very different considering the absorption properties of NIR radiation. Some green pigments strongly absorb NIR radiation, while some green pigments absorb very little. That is why we have introduced the acronym Z as numerical information on the absorption of NIR light for all colorants, with a range from zero to ten. Painters are trained to mix colors with respect to their Z values. Dual images are produced. The NIR camera separates the drawing, the image, depending on the amount of Z color. The painter succeeds in arranging the colors so discreetly that two images are taken in the same place, one of which is seen by the naked eye, while the other requires an NIR camera to be seen. The idea of a VIS / NIR painting is accepted with the realization that there are many video surveillance (NIR) cameras around us: on the streets, in restaurants, in banks, in public entrances and entrances to private houses in general. The NIR design is used on documents, diplomas and banknotes as a general security method in graphic technology
Svakom pigmentu i bojilu dodjeljujemo informaciju o njihovoj apsorpciji svijetlosti u bliskom infracrvenom spektru (NIR) na 1000 nm. Općenito, crveni pigment, žuti, cijan plavi, naranđasti, bijeli i drap (svjetlo smeđi) ne apsorbiraju NIR svjetlost. NIR kamera ih ne razlikuje, ne prepoznaje ili "ne vidi", pa je za njih NIR fotografija bijela. Te boje su označene sa slovom V (vidljive, VIS). Prostor zelenih pigmenata (na našem jeziku, "zeleno" = Z) je veoma različit što se tiče apsorpcije NIR radijacije. Neki zeleni pigmenti jako apsorbiraju NIR radijaciju, dok neki zeleni pigmenti apsorbiraju vrlo malo. To je razlog zašto smo uveli akronim Z kao numerička informacija za apsorpciju NIR svjetlosti za sva bojila; u rasponu od nule do deset. Slikare smo uvježbali da miješaju bojila s respektom prema njihovoj Z vrijednosti: Proizvode se dvostruke slike. NIR kamera razdvaja crteže, slike, ovisno o količini Z boja. Slikar uspijeva uređivati boje tako diskretno da su dvije slike na istom mjestu; jedna koja je vidljiva golim okom, dok je za drugu potrebna NIR kamera da bi ju vidjeli. Ideja o VIS / NIR slikarstvu je prihvaćena i realizirana budući da u našoj okolici postoje mnoge nadzorne (NIR) kamere: na ulici, u restoranima, u bankama, na društvenim ulazima te općenito na ulazima u privatne kuće. NIR dizajn se koristi na dokumentima, diplomama i novčanicama kao opća sigurnosna metoda u grafičkoj tehnologiji.
Bibliografske bilješke na kraju teksta.
Abstract ; Sažetak.
Keywords: Slike -- Infracrveni spektar -- NIR tehnologija